Dysmenorrhoea and Menstrual Hygiene Practices Among Rural Adolescent Girls in Bangladesh - Urmy, Nushrat Jahan; Rahman, Md Anisur; Adhikary, Sanchita; Ruma, Kazi Sadeka; Sultana, Arifa (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: The connection between menstrual hygiene management and overall health of female adolescents is undeniable. Objective: This study aims to determine the relationship between dysmenorrhoea and menstrual hygiene practices among rural female adolescents. Methods: This cross-sectional, descriptive study was conducted among 312 adolescent girls (aged between 13 and 19 years) in the selected rural areas of Nawabganj upazila under Dhaka district, Bangladesh, between January and December of 2017. Adolescents who were unmarried, attained menarche at least 2 years before study period and who were willing to participate were included in this study. However, Adolescents who were suffering from any diseases such as, ovarian cysts, endometriosis, pelvic inflammatory diseases, and of those who were taking oral contraceptive pill for any hormonal problem were excluded from the study. Data collection was done using a semi-structured questionnaire which included participants’ age, height, weight, menstrual history, clinical features of dysmenorrhoea, medication history, menstrual hygiene practices and facilities. Data was collected through face-to-face interview. The Verbal Multidimensional Scoring System (VMSS) was used to assess the severity of dysmenorrhoea by evaluating multiple dimensions, including pain intensity, impact on daily activities, systemic symptoms, and analgesic requirements. Results: 70.5% of the rural adolescent girls experienced some forms of dysmenorrhoea – 25.3%, 23.1% and 22.1% reported mild, moderate and severe dysmenorrhoea respectively. No association was observed between factors of menstrual hygiene practices and dysmenorrhoea among the adolescents (p>0.05). Surprisingly, institutional separate toilets and disposal facility for sanitary cloths or pads was related to more prevalence of dysmenorrhoea (p<0.05). Conclusion: Access to menstrual products and hygiene facilities needs to be ensured in schools, workplaces and public institutions to manage menstruation with comfort and dignity for adolescent girls. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 212-217